GROWTH AND DRY MATTER PRODUCTION ON YIELD OF RICE (Oryza sativa L.) VARIETIES UNDER ALTERNATE WETTING AND DRYING IN PUDDLED SOIL - D. SRINIVASA CHARY, M. SHARATH CHANDRA, K. AVIL KUMAR, M. MADHAVI and (The Journal of Research, PJTSAU, 2019)
Food security in Asia is challenged by increasing food demand and threatened water availability. Geometric growth of population and arithmetic increase in food grain production leave a vast gap in food supply. In India and Telangana, rice occupies an area of 44.10 M ha and 14.15 lakh ha, respectively during 2014-2015 (DoES, 2015). As per the concepts of water foot print and virtual water to produce one kg of rice 3000-5000 liters of water is required. Being a water-intensive crop, cultivation of paddy has been a big drain on water resources. Rice is a heavy water consumer but water for rice production is becoming scarce and expensive due to the increased demand for water from the ever growing population and industries (Chowdhury et al. 2014). Irrigated lowland rice not only consumes more water but also causes wastage of water resulting in degradation of land. In recent years to tackle this problem, many methods of cultivation have been developed. Among the different methods of water-saving irrigation, the most widely adopted is Alternate Wetting and Drying (AWD) irrigation method (Li and Barker, 2004).